EFL TEACHERâS BELIEF AND PRACTICE ON INTEGRATING ICT IN THE CLASSROOM: A CASE STUDY ON THE IMPLEMENTATION OF SAMR MODEL IN TEACHING READING DESCRIPTIVE TEXT AT MA ASSALAM, SUKOHARJO - Budiman, Asep Budiman; Rahmawati, Rani; Ulfa, Rizky Amalia (Jurnal Penelitian Humaniora, 2018)
21st century learning demands the integration of Information and CommunicationTechnology (ICT) in teaching and learning process. Regarding this issue, this research isaimed at investigating English as a foreign language (EFL) teacherâs belief and practices onthe integration of ICT in English language teaching. To reach the objective, a case study onan individual teacher was used in this research. The participant was purposively andtheoretically selected because she was considered as the informant who could givesufficient information to answer the research questions. Teacherâs interview and classroomobservation were used as the data collecting techniques. Iterative data collection andanalysis were conducted continuously till theoretical pattern of concepts and categorieswere achieved. The Substitution Augmentation Modification Redefinition (SAMR) modelwas used as the data analysis tool resulted from the classroom observation to reveal to whatextent the teacher implements ICT integration. The results of this research indicate that theteacher believes that integrating ICT is very important as ICT has ability to maketransformation of all educational aspects by making use of it to reachinstructional objectives then the quality of teaching and learning will improve. Theresults also indicate that there is no discrepancy between belief and practice as the teacherhas been integrating ICT in the classroom. However, the teacher is still on the substitutionand augmentation stages in integrating ICT and hardly achieves modification and redefinitionstages. These results suggest that teachers be prepared for ICT integration to create moremeaningful learning in the classroom.